Perbandingan Bata Interlock Desain Keylock Brick dan Multi Gridlock terhadap Kuat Tekan - Amanda, Rachel; Rochmah, Nurul (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
The primary problem in using conventional red bricks as wall materials lies in their low construction efficiency, high dependence on mortar, and inconsistent structural quality, which makes them less suitable for modern construction demands that require speed, accuracy, and sustainability. These limitations create a strong need for innovative building materials capable of improving mechanical performance while enhancing construction efficiency. This study aims to analyze the influence of interlocking geometry variations in concrete bricks, specifically the Keylock Brick and Multi Gridlock types, on compressive strength, and to compare their performance with conventional red bricks to determine the most structurally optimal design. The research employs a quantitative experimental approach, where specimens are produced based on the predetermined geometric designs. Compressive strength tests are conducted using a Compression Testing Machine (CTM) to measure the maximum applied load. Data analysis is performed descriptively and comparatively based on the surface area and compressive strength values obtained from each sample. The results indicate that interlocking geometry significantly affects compressive strength performance. The Keylock Brick type achieves an average compressive strength of 100.03 kg/cm², classified as a solid concrete brick of quality level I according to SNI 03-0349-1989. Meanwhile, the Multi Gridlock type records an average compressive strength of 60.48 kg/cm², categorized as a hollow concrete brick of quality level II. Both values are higher than that of conventional red bricks, which average 31.68 kg/cm². These findings demonstrate that optimizing interlocking geometry can substantially enhance the structural performance of concrete bricks, offering a more efficient and sustainable alternative for modular construction applications